Entrepreneurial Traits and the Distribution of Poultry Farm Entrepreneurs in Delta State, Nigeria - Isiorhovoja, R. A; Inoni, O. E; Ogisi , O. D (Asian Journal of Agriculture and Rural Development, 2013)
The authors attempted to ascertain the entrepreneurial potential of poultry farmers in Delta State using farmers’ scores in six entrepreneurial traits measured on a five-point Likert scale. The study covered the population of 275 poultry farmers in the State. The objectives were to ascertain the level of entrepreneurial traits of Poultry farmers and to determine the distribution of poultry farm entrepreneurs by category, namely; low, average and high potential, across the three agricultural zones. The hypotheses tested were that entrepreneurial traits of poultry farmers were not above average and that there was no significant variation in poultry farmers’ entrepreneurial potentials across the three agricultural zones. Primary data were collected using copies of a structured questionnaire. By using analysis of variance and test of differences between a test value of 3.4, major findings were that poultry farmers were above average in three entrepreneurial traits but with significant variation across the zones; that entrepreneurial potential was generally below average, finally, that the three categories of poultry farm entrepreneurs were randomly distributed across the zones. The authors concluded that while there may not be any inherent biases in drawing sample of poultry farmers across the State for development projects purposes, there may be differences in cost implications for farmers’ entrepreneurial development.